The Comparison of the Effect of Mental Rotation and Phonological Awareness Training on Accuracy, Speed and Comprehension in Students with Dyslexia in City of Tabriz, 2015-2016 - Ramin Habibi-Kaleybar (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2017)
Abstract Background: The problem of learning disabilities is the reason of academic backwardness of students and dyslexia is considered the most common of these disorders.Therefore, the present study aimed to investigate the comparison of the effectiveness of mental rotation and phonological awareness training on reading performance of students with dyslexia. Materials and Methods: The design of the study was quasi-experimental in pre-test and post- test with control group. Statistical population composed of all dyslexic students in the city of Tabriz in 2015-2016. The sample of present research consisted of 45 students with dyslexia who were selected via available sampling and then were assigned randomly to experimental) phonological awareness and mental rotation training) and control groups(n=15 in each). To collect data, revised Wechsler intelligence scale for children and reading improvement and dyslexia test were used. Multivariate Covariance (MANCOVA) was used to analyze the data. Results: Findings indicated that scores of mental rotation and phonological awareness training have a significant effect on reading performance of dyslexic students compared with control group (p<0.001). Furthermore, there is no difference between mental rotation and phonological awareness training effectiveness on reading performance of dyslexic students (p>0.05). Conclusion: It can be concluded that mental rotation and phonological awareness training are effective on accuracy, speed and comprehension of reading in students with dyslexia.